2021
DOI: 10.3390/toxins13020085
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Antibacterial Activity of Gliotoxin Alone and in Combination with Antibiotics against Staphylococcus aureus

Abstract: Multidrug-resistant bacteria such as methicillin-resistant Staphylococcus aureus (MRSA) is one of the major causes of hospital-acquired and community infections and pose a challenge to the human health care system. Therefore, it is important to find new drugs that show activity against these bacteria, both in monotherapy and in combination with other antimicrobial drugs. Gliotoxin (GT) is a mycotoxin produced by Aspergillus fumigatus and other fungi of the Aspergillus genus. Some evidence suggests that GT show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
0
16
0
2
Order By: Relevance
“…It is a well-known mycotoxin produced by species of Aspergillus, Penicillium, Fusarium and Trichoderma, fungi which are eutrophic and reside in nutrient-rich habitats such as composting debris. In these microbe-rich environments they have to compete for survival against a large diversity of fungi and bacteria by rapid growth and production of toxic metabolites Toxic effects of GTX against fungi (Carberry et al 2012 ) and bacteria (Esteban et al 2021 ) are due to redox-cycling of a disulphide-bridge. Among the toxic effects are expression of proteins, disturbance of enzymes, and leakage of mitochondrial membranes.…”
Section: Beneficial Use Of a Toxin: Gliotoxinmentioning
confidence: 99%
“…It is a well-known mycotoxin produced by species of Aspergillus, Penicillium, Fusarium and Trichoderma, fungi which are eutrophic and reside in nutrient-rich habitats such as composting debris. In these microbe-rich environments they have to compete for survival against a large diversity of fungi and bacteria by rapid growth and production of toxic metabolites Toxic effects of GTX against fungi (Carberry et al 2012 ) and bacteria (Esteban et al 2021 ) are due to redox-cycling of a disulphide-bridge. Among the toxic effects are expression of proteins, disturbance of enzymes, and leakage of mitochondrial membranes.…”
Section: Beneficial Use Of a Toxin: Gliotoxinmentioning
confidence: 99%
“…To date, a lot of data has been accumulated on the effect of gliotoxin on various eukaryotic cells [15]. Data on gliotoxin antimicrobial properties are accumulating [19][20][21], which allows gliotoxin to be considered in antibiotic monotherapy or in combination [18] Existing studies had shown very quickly uptake rate of gliotoxin by various mammalian cells, most of the toxin becomes cell associated within 10 min [22]. In our work we have found significant decreasing in free gliotoxin during first 10 minutes, which is consistent with the data obtained on fungi [23].…”
Section: Discussionmentioning
confidence: 99%
“…The first study of the antibacterial action of gliotoxin refers to the first half of the 20th century [11, 17, 18]. To date, a lot of data has been accumulated on the effect of gliotoxin on various eukaryotic cells [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La técnica de microdilución se realizó colocando 100 µL de caldo Mueller Hinton en cada pozo de una placa de 96 pozos, añadiendo concentraciones seriadas de 20 a 0.078 µM de BEA para las cepas de S. aureus, y de 60 a 10 µM para S. typhimurium, así como concentraciones seriadas de 1.28 mM a 0.019 µM de lincomicina, concentraciones seriadas de 0.25 a 0.0039 µM para oxacilina y concentraciones seriadas de 20 µM a 0.15 nM para ciprofloxacino. A continuación, ,se inoculó cada pozo con 5 µL de la suspensión bacteriana ajustada a 1 en la escala de McFarland, equivalente a 1.5x10 6 UFC, finalmente la placa fue incubada a 37°C durante 24 horas y leída en un lector de placas Synergy HT (BioTek ® ) a 600nm, para determinar los pozos en los que hubo crecimiento bacteriano (Esteban et al, 2021;Morales-Ubaldo et al, 2020). Se utilizó como control negativo 50 mM de lincomicina, como control positivo solo medio de cultivo con el inóculo bacteriano, un control con solamente medio de cultivo para descartar contaminación en la placa y un control con medio de cultivo, inóculo y vehículo para descartar cualquier efecto que pudiera tener el vehículo en el crecimiento bacteriano.…”
Section: Determinación De La Concentración Mínima Inhibitoriaunclassified